Restoration of Justice Through Rehabilitation As a Critical Review of The Effectiveness of Article 54 of The Narcotics Law As a Paradigm of Modern Criminal Prosecution - Maskanah, Ummi; Mulyana, Yusep (Jurnal Hukum dan Keadilan, 2025)
Restorative justice demands a shift from punishment to rehabilitation. Article 54 of the Narcotics Law mandates rehabilitation as an obligation for addicts, shifting the criminal paradigm from punishment to protection and rehabilitation. This rehabilitation reflects the values of restorative justice, which emphasize social and personal recovery from drug abuse. This study aims to examine the position of Article 54 of Law Number 35 of 2009 concerning Narcotics within the framework of modern criminal justice and the concept of restorative justice, as well as to examine the implementation of rehabilitation for drug addicts as a form of recovery approach compared to punishment. The method used is normative juridical with a statutory and conceptual approach, through an analysis of positive legal norms and their relevance in the criminal justice system in Indonesia. The results of the discussion indicate that Article 54 of Law No. 35 of 2009 has an important position in the framework of modern criminalization and restorative justice , by emphasizing medical and social rehabilitation for addicts and victims of drug abuse, rather than punishment. In its implementation, although normatively it reflects a healing approach and protection of human rights, implementation in the field still faces obstacles such as limited facilities, social stigma, and weak support from officials, thus requiring strengthening of policies and institutions.